2003
DOI: 10.1016/s1534-5807(03)00122-9
|View full text |Cite
|
Sign up to set email alerts
|

Syntaxin 2 and Endobrevin Are Required for the Terminal Step of Cytokinesis in Mammalian Cells

Abstract: The terminal step of cytokinesis in animal cells is the abscission of the midbody, a cytoplasmic bridge that connects the two prospective daughter cells. Here we show that two members of the SNARE membrane fusion machinery, syntaxin 2 and endobrevin/VAMP-8, specifically localize to the midbody during cytokinesis in mammalian cells. Inhibition of their function by overexpression of nonmembrane-anchored mutants causes failure of cytokinesis leading to the formation of binucleated cells. Time-lapse microscopy sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
166
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(180 citation statements)
references
References 31 publications
10
166
0
Order By: Relevance
“…Cells failing cytokinesis in the presence of the ADPRT activity complete furrowing but fail to resolve the midbody and eventually fuse to form binucleated cells. This mode of cytokinesis block is similar to the cytokinesis failure observed in cells expressing dominant negative mutants of syntaxin-2 or endobrevin (33). We have found that Crk adaptor proteins localize to the midbody after cleavage furrow formation and are required to recruit syntaxin-2 (S.H.S., K. Mostov, and J.E., unpublished results).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Cells failing cytokinesis in the presence of the ADPRT activity complete furrowing but fail to resolve the midbody and eventually fuse to form binucleated cells. This mode of cytokinesis block is similar to the cytokinesis failure observed in cells expressing dominant negative mutants of syntaxin-2 or endobrevin (33). We have found that Crk adaptor proteins localize to the midbody after cleavage furrow formation and are required to recruit syntaxin-2 (S.H.S., K. Mostov, and J.E., unpublished results).…”
Section: Discussionsupporting
confidence: 69%
“…Published studies have demonstrated that, at late stages of cytokinesis, the v-SNARE Endobrevin͞VAMP8 and the t-SNARE Syntaxin-2 are localized to the midbody, a specialized structure in the cytoplasmic bridge connecting the daughter cells (33). Their function is required for the final step in cytokinesis, abscission, in which the membranes undergo separation.…”
Section: Adprt Activity Inhibits Cytokinesis By Blocking Syntaxin-2 Mmentioning
confidence: 99%
“…VAMP-8, one of the SNARE types localized to the endosomes, had been shown to play important roles, from homotypic fusion of early and late endosomes (15,18), exocytosis of vesicles (14,19,28,29), cytokinesis (30), to its role in phagocytosis modulation (our current findings). VAMP-8 forms complexes with Syn-7, Syn-8, and Vti1b, which mediates homotypic fusion of early and late endosomes (15,17,18).…”
Section: Discussionsupporting
confidence: 58%
“…Overexpression of VAMP-8 in MIN6 cells significantly increased GABA release (14), and although the precise complex involved was not defined, it is likely to involve the complex required for exocytosis. VAMP-8 has also been shown to be important in the terminal step of cytokinesis in the mammalian cells (30), where it was localized to the mid-body of late telophase NRK cells and that introduction of VAMP-8 lacking the C-terminal transmembrane region into MDCK cells resulted in the formation of binucleated cells.…”
Section: Discussionmentioning
confidence: 99%
“…All fusion proteins contain the extracytoplasmic domain and signal peptide of CD16, the transmembrane domain of CD7 and the full-length cytoplasmic tail of PC1 (FLM-PC1, residues 4077-4302 of human PC1), the N-terminal half of the tail (NTM-PC1, residues 4077-4168), or the C-terminal half of the tail (CTM-PC1, residues 4191-4302). Constructs were transfected into MDCK cells that had been stably transfected for expression of the TET-repressor (37), and stable clones were selected.…”
Section: Pc1 Constructs and Generation Of Stable Mdck Cell Linesmentioning
confidence: 99%